Cerita Nusantara: On CSR Program Innovation and Optimization of Child Growth and Development : (A Study at PT PLN Nusantara Power UP Muara Karang) - Sarika Apriyeni Gopar; Agus Maulana; Tri Nofi Nur Antoro; Hanafi Faris Fauzi; Monica Anindita Firnadi; Trie Dinda Putri (Global Writing Academica Researching and Publishing, 2025)
This study analyzes the implementation of the Cerita Nusantara social innovation carried out through the CSR program of PT PLN Nusantara Power UP Muara Karang. A descriptive qualitative approach was employed to examine efforts to optimize child growth and development in Penjaringan District through the Cerita Nusantara program. The findings indicate that the social innovation has succeeded in creating a sustainable community empowerment ecosystem focused on fulfilling children’s developmental needs. Other significant findings reveal that: (1) Efforts to optimize child growth and development through Cerita Nusantara are implemented using a holistic approach. Parents are equipped with the knowledge and skills to support their children’s development actively. (2) CSR interventions in collaboration with the KITA Community serve as the foundation for nutritional optimization during the first 1,000 days of life (HPK) in Penjaringan District. (3) Within three years, the Cerita Nusantara social innovation has successfully improved the economic conditions of the KITA Community.